ACCREDITATION-BASED QUALITY BUILDING RECONSTRUCTION TOWARDS EXCELLENT PTKI - Buyung Syukron; Muhammad Mujib Baidhowi; Fitri Sari; Sarah Ayu Ramadhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
The main problem and spectrum that is always faced by Indonesian Islamic Higher Education (PTKI) is the low and not optimal quality of the three missions of higher education, namely education, research, and service. Various problems related to this are increasingly visible from the fact that the system's alignment, and policies to the institutional leadership structure seem to leave quality as an agenda, and programs are not prioritized. Therefore, the aspects and functions of quality management at PTKI are important. Improvement in Quality Management in PTKI should be oriented to build a quality culture in all components and elements of the academic community The most urgent quality culture for PTKI that must be done in meeting quality standards is to strengthen the system and meet the accreditation standards that have been required to achieve maximum results. In the context of accreditation, building quality must also strengthen the position in the sector of coordination, synchronization, and supervision between the entire academic community. The most urgent quality culture for PTKI that must be done in meeting quality standards is to strengthen the system and meet the accreditation standards that have been required to achieve maximum results. The transformation of seven criteria into 9 criteria in the accreditation system has consequences and consistency in the assessment aspect that leads to the outcomes (achievements of the process and usefulness) that have been passed by PTKI with various implementations based on its quality standards/guidelines. This research uses qualitative methods that are descriptive-analytical and seeks to analyze how the supporting factors of quality culture exist PTKI. This study uses a qualitative method that is descriptive-analytical and seeks to analyze how the factors supporting the quality culture in PTKI.